The use of the offer of compromise/scheme of arrangement provisions of Section 311 of the Companies Act 61 of 1973 as a take-over mechanism - Bloch, A. M. (Department of Commercial Law, 2023)
Since 1987, there has been a flurry of decisions relating to S311 of the Companies Act 61 of 1973 ("the Act") reported in the South African Law Reports. Many of the decisions concern the "standard" offer of compromise, which was previously used by third parties to acquire the creditors claims against (and shares in) companies in liquidation ( normally provisional), thereby freeing the company from liquidation and creating the potential for considerable taxation advantages to accrue to the acquirer. However, two recent decisions in the Transvaal, both of which concerned schemes of arrangement under S311 involving the acquisition of shares in trading companies, highlight important questions in regard to the use of the S311 procedure as a take-over mechanism.